Perancangan Showroom Mobil Mini di Surabaya - Lintu Tulistyantoro, Darren Louis Cahyadi (Intra, 2016)
MINI is a small car produced by the British Motor Corporation (BMC) and its successors from 1959 until 2000. The original model of the car is considered as the icon of the British in the 1960s. The design concept in this design is "Branding in Perfection" which means that this concept carries the branding image as a concept, and perfection means we bring perfection in design in accordance with the philosophy of the meaning of the logo of MINI. The theme of the design is contemporary design, means the design style of the room is influenced by modern impression and always follows the latest design trend, but comfortable and functional as well.